2017
DOI: 10.1002/adfm.201700278
|View full text |Cite
|
Sign up to set email alerts
|

Structure Sorting of Large‐Diameter Carbon Nanotubes by NaOH Tuning the Interactions between Nanotubes and Gel

Abstract: The structure separation of synthetic single-wall carbon nanotube (SWCNT) mixture species with diameters larger than 1.2 nm still remains a challenge. Here, an NaOH-assisted gel chromatography method is used for the structure separation of the SWCNT mixture with a diameter range of 1.2-1.7 nm, in which NaOH is used to tune the interaction between distinct (n, m) SWCNTs and gel. Incrementally increasing NaOH concentration in SWCNT dispersion selectively enhances the adsorbability of different-structure SWCNTs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…Mechanistic insight into this correlation should also necessarily consider the thermodynamically driven nature of the SWNT desorption process, which has been demonstrated experimentally by the irreversible nature of SWNT/gel binding in the presence of 70 mM SDS. Specifically, SWNT bound to Sephacryl is not released upon the addition of neat 70 mM SDS but rather only in the presence of additional dielectric screening (introduction of 175 mM SDS or NaCl/SDS mixtures) does a fraction of the SWNT desorb from the gel. , This observation demonstrates that a thermodynamic stability, as opposed to a kinetic equilibrium due to a gradient in SWNT concentration, is responsible for driving the process of SWNT desorption from gels.…”
Section: Results and Discussionmentioning
confidence: 98%
“…Mechanistic insight into this correlation should also necessarily consider the thermodynamically driven nature of the SWNT desorption process, which has been demonstrated experimentally by the irreversible nature of SWNT/gel binding in the presence of 70 mM SDS. Specifically, SWNT bound to Sephacryl is not released upon the addition of neat 70 mM SDS but rather only in the presence of additional dielectric screening (introduction of 175 mM SDS or NaCl/SDS mixtures) does a fraction of the SWNT desorb from the gel. , This observation demonstrates that a thermodynamic stability, as opposed to a kinetic equilibrium due to a gradient in SWNT concentration, is responsible for driving the process of SWNT desorption from gels.…”
Section: Results and Discussionmentioning
confidence: 98%
“…We can prepare higher purity but a tiny amount of the (11,–5) SWCNTs with a CD norm value of 93 mdeg by controlling the pH in gel chromatography as described in recent work . By comparing the absorption spectra (Figure S10), we found that the samples used in this work contain impurities, such as amorphous carbon, which causes additional background absorption.…”
mentioning
confidence: 77%
“…SWNTs with large diameters (such as arc-discharged SWNTs) have little curvature difference and narrow diameter distributions among the type of nanotubes; thus, their separation according to chirality has not been successful. Nevertheless, Yang et al successfully separated s-SWNTs according to their diameters with pH control and multi-column chromatography [ 128 ]. Oxidation of SWNTs occurs not only through the addition of acidic solutions but also by changes in the temperature of the aqueous solution.…”
Section: Allyl Dextran-based Gelsmentioning
confidence: 99%